If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(z+4)=96
We move all terms to the left:
6(z+4)-(96)=0
We multiply parentheses
6z+24-96=0
We add all the numbers together, and all the variables
6z-72=0
We move all terms containing z to the left, all other terms to the right
6z=72
z=72/6
z=12
| 34x-862=22 | | x/16+9x/10=x/14 | | 13+9w=49 | | (2p-5)=(p+5 | | (r+5)(r+13)=0 | | 30x^2-20x-160=0 | | y-98/2=1 | | 7y+1=92 | | 340=1,5*x | | (14x+17)=(19x-23) | | 340=1,5.f | | f-80/2=6 | | -7n^2-86n-336=0 | | (6x+11)=(10x-45) | | (4x+3)=12 | | 24x^2+16x-3=0 | | 24x+16x-3=0 | | 55x+3=625x+2 | | 2(2x-3)=6x+2-2x-9 | | 4.4g+10=1.4g+22 | | b45×-2=0 | | 5(m-1)=3m+10+5m | | 2x+1x+6=3x+6 | | (3x-3)+(x-17)+(x)=180 | | 23=v/5+17 | | 6y=9=3(2y+3) | | -3f(-3f-6=) | | 9x²-1=(3x+1)(3x-1) | | -b/10=18 | | r+25/7=5 | | (2x+48)+(x-12)+(x)=180 | | p+2/5=20 |